1999
DOI: 10.1017/s0266467499001029
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, mineralogy and microbiology of termite mound soil eaten by the chimpanzees of the Mahale Mountains, Western Tanzania

Abstract: Subsamples of termite mound soil used by chimpanzees for geophagy, and topsoil never ingested by them, from the forest floor in the Mahale Mountains National Park, Tanzania, were analysed to determine the possible stimulus or stimuli for geophagy. The ingested samples have a dominant clay texture equivalent to a claystone, whereas the control samples are predominantly sandy clay loam or sandy loam, which indicates that particle size plays a significant role in soil selection for this behaviour. One potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 40 publications
4
38
1
Order By: Relevance
“…The seasonal development of aquic conditions at the valley bottom and fringe sites was indicated by the greyish soil matrix color with redoximorphic features and the high groundwater Our results (Fig. 1) support Mahaney et al (1999) and Ketch et al (2001), who found only subtle differences in clay mineralogy between the mound structures and adjacent soils. These data represent a contrasting evidence to that of soil particle distribution data in Table 1 that showed substantial enrichment with clay particles in the mound structures relative to the adjacent natural soil horizons (Abe et al 2009a(Abe et al , 2009b.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The seasonal development of aquic conditions at the valley bottom and fringe sites was indicated by the greyish soil matrix color with redoximorphic features and the high groundwater Our results (Fig. 1) support Mahaney et al (1999) and Ketch et al (2001), who found only subtle differences in clay mineralogy between the mound structures and adjacent soils. These data represent a contrasting evidence to that of soil particle distribution data in Table 1 that showed substantial enrichment with clay particles in the mound structures relative to the adjacent natural soil horizons (Abe et al 2009a(Abe et al , 2009b.…”
Section: Discussionsupporting
confidence: 77%
“…These findings suggest that termites have a preference for clay mineral species and that their nest-building activity affects soil clay mineralogy. In contrast, Mahaney et al (1999) and Ketch et al (2001) documented very little disparity in clay mineralogy between Macrotermitinae mounds and adjacent soils. The contradictory results in the previous reports indicate that further research is needed on termitesʼ clay mineral preference and the resultant changes in soil clay mineralogy in their mounds and nests.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Lee and Wood 1971;Lal 1988;Mahaney et al 1999) and as such represent resource islands in relatively nutrient poor savanna environments (Frost 1996). Plant species richness generally follow a hump-shaped relationship, increasing with increasing productivity until it peaks and the diversity declines with a further productivity increase (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies on ecological (Lee and Wood 1971;Rogers 1972;Pomeroy 1976Pomeroy , 1978McComie 1981;Wood 1988;Conacher 1990 and1995;Anderson and Jacklyn 1993;Ekundayo and Aghatise 1997;Dangerfield et al 1998), soil nutrient cycling, and soil metabolism (Abbadie and Lepage 1989) aspects of mounds have been discussed. Earlier workers have discussed the physical and chemical changes, involved in the formation of termite soils (Lee and Wood 1971;Mahaney et al 1996Mahaney et al , 1999. There is an extensive literature on termites and their structures (Mando and Miedema 1997) dealing with their biological (Jungerius et al 1999), agricultural (Black and Okwakol 1997), microbiological (Holt 1998), and paleoclimatological (Genise 1997) aspects.…”
Section: Introductionmentioning
confidence: 99%